Osteoarthritis and cardiovascular disease: A Mendelian randomization study - Zhao Wang; Chan Kang; Pai Xu; Shuyi Zhang; Jae Hwang Song; Dongyang Wang; Shuai Yuan; Hyun Jong Lee; Meng Zhang; Zhihui Wang; Hao Sun; Ruobing Fan (Frontiers in Cardiovascular Medicine, 2022)
ObjectiveThis Mendelian randomization (MR) study aimed to investigate the causal relationship between osteoarthritis (OA) and cardiovascular disease (CVD).MethodsFrom a genome-wide association study of European ancestry, we selected single nucleotide polymorphisms for two types of OA, knee osteoarthritis (KOA) and hip osteoarthritis (HOA), as instrumental variables. We evaluated three types of CVD: coronary heart disease (CHD), heart failure (HF), and stroke. We used the traditional inverse variance weighting (IVW) method and other methods to estimate causality. Heterogeneity and sensitivity tests were also applied. Finally, we conducted a MR analysis in the opposite direction to investigate reverse causality.ResultsIVW analysis showed that HOA significantly affected the incidence of HF [odds ratio (OR): 1.0675; 95% confidence interval (CI): 0.0182–0.1125, P = 0.0066]. HOA significantly affected the incidence of stroke (OR: 1.1368; 95% CI: 1.0739–1.2033, P = 9.9488e-06). CHD could dramatically affect the incidence of KOA (OR: 0.9011; 95% CI: 0.8442–0.9619, P = 0.0018). The rest of the results were negative.ConclusionsOur results revealed a potential causal relationship between HOA and risk of HF, and a potential causal relationship between HOA and risk of stroke. Our findings also suggested that CHD has a significant causal relationship with the risk of KOA. This paper may provide new ideas for the treatment of OA and CVD.